iSanXoT: A standalone application for the integrative analysis of mass spectrometry-based quantitative proteomics data - Rodríguez, Jose Manuel; Jorge, Inmaculada; Martinez-Val, Ana; Barrero-Rodríguez, Rafael; Magni, Ricardo; Núñez, Estefanía; Laguillo, Andrea; Devesa, Cristina A.; López, Juan A.; Camafeita, Emilio; Vázquez, Jesús (Computational and structural biotechnology journal, 2024)
Many bioinformatics tools are available for the quantitative analysis of proteomics experiments. Most of these tools use a dedicated statistical model to derive absolute quantitative protein values from mass spectrometry (MS) data. Here, we present iSanXoT, a standalone application that processes relative abundances between MS signals and then integrates them sequentially to upper levels using the previously published Generic Integration Algorithm (GIA). iSanXoT offers unique capabilities that complement conventional quantitative software applications, including statistical weighting and independent modeling of error distributions in each integration, aggregation of technical or biological replicates, quantification of posttranslational modifications, and analysis of coordinated protein behavior. iSanXoT is a standalone, user-friendly application that accepts output from popular proteomics pipelines and enables unrestricted creation of quantification workflows and fully customizable reports that can be reused across projects or shared among users. Numerous publications attest the successful application of diverse integrative workflows constructed using the GIA for the analysis of high-throughput quantitative proteomics experiments. iSanXoT has been tested with the main operating systems. Download links for the corresponding distributions are available at https://github.com/CNIC-Proteomics/iSanXoT/releases. [Display omitted]